Perbandingan Teori Pembentukan Alam Semesta : Big Bang Vs Steady State dalam Perspektif Kosmografi - Muhammad Arif; Elsa Kardiana; Suryana Daulay; Dzuriati’ A Yuni Aceh; Yurdan Sihotang; Tasya Maria Natalia Pangaribuan; Jernih Margaretha Siahaan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to compare two main theories in modern cosmology, namely the Big Bang Theory and the Steady State Theory, using a descriptive cosmographic approach. This study is motivated by the lack of deep understanding as well as the limited Indonesian literature discussing the fundamental differences between the two theories. By employing a qualitative method through literature review, this research examines the characteristics, advantages, and limitations of each theory based on the latest scientific evidence and cosmographic perspectives. The analysis results show that the Big Bang Theory has strong support from observational evidence, such as cosmic microwave background radiation (CMB), galaxy redshift, and the distribution of light elements, which reinforces the narrative of the expansion and evolution of the universe. In contrast, the Steady State Theory is considered less relevant due to the absence of observational evidence for the creation of new matter and its inability to explain structure and the dynamics of the universe that are currently observed.